Apresente uma derivação à extrema direita (DED) da sentença x = a + a * (b - c) + (b - c) * d sobre a gramática a seguir.
G = ({A, E, T, F, V}, {a, b, c, d, x, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < V > = < E >
< E > -> < E > + < T > | < E > - < T > | < T >
< T > -> < T > * < F > | < T > / < F > | < F >
< F > -> ( < E > ) | < V >
< V > -> a | b | c | d | x }
< A >
< V > = < E >
< V > = < E > + < T >
< V > = < E > + < T > * < F >
< V > = < E > + < T > * < V >
< V > = < E > + < T > * d
< V > = < E > + < F > * d
< V > = < E > + ( < E > ) * d
< V > = < E > + ( < E > - < T > ) * d
< V > = < E > + ( < E > - < F > ) * d
< V > = < E > + ( < E > - < V > ) * d
< V > = < E > + ( < E > - c ) * d
< V > = < E > + ( < T > - c ) * d
< V > = < E > + ( < F > - c ) * d
< V > = < E > + ( < V > - c ) * d
< V > = < E > + ( b - c ) * d
< V > = < E > + < T > + ( b - c ) * d
< V > = < E > + < T > * < F > + ( b - c ) * d
< V > = < E > + < T > * ( < E > ) + ( b - c ) * d
< V > = < E > + < T > * ( < E > - < T > ) + ( b - c ) * d
< V > = < E > + < T > * ( < E > - < F > ) + ( b - c ) * d
< V > = < E > + < T > * ( < E > - < V > ) + ( b - c ) * d
< V > = < E > + < T > * ( < E > - c ) + ( b - c ) * d
< V > = < E > + < T > * ( < T > - c ) + ( b - c ) * d
< V > = < E > + < T > * ( < F > - c ) + ( b - c ) * d
< V > = < E > + < T > * ( < V > - c ) + ( b - c ) * d
< V > = < E > + < T > * ( b - c ) + ( b - c ) * d
< V > = < E > + < F > * ( b - c ) + ( b - c ) * d
< V > = < E > + < V > * ( b - c ) + ( b - c ) * d
< V > = < E > + a * ( b - c ) + ( b - c ) * d
< V > = < T > + a * ( b - c ) + ( b - c ) * d
< V > = < F > + a * ( b - c ) + ( b - c ) * d
< V > = < V > + a * ( b - c ) + ( b - c ) * d
< V > = a + a * ( b - c ) + ( b - c ) * d
x = a + a * ( b - c ) + ( b - c ) * d